Deposition of palladium catalyzed copper films by the displacement of two immiscible supercritical phases and subsequent reaction - Kim, Jaehoon; Carbonell, Ruben G. (ROYAL SOC CHEMISTRY, 2010)
Palladium (Pd) catalyzed copper (Cu) films were produced by forming films of Cu(II) compound (Cu(hfac)(2)center dot H(2)O) and Pd(II) compound (Pd(hfac)(2)) on silicon oxide (SiO(x)) and titanium nitride (TiN) substrates using a Displacement from two Immiscible Supercritical Phases (DISPs) technique followed by reduction of the organometallic compounds films in hydrogen at 200 degrees C. The morphology of Cu films was observed using scanning electron microscopy (SEM) and atomic force microscopy (AFM). In the absence of Pd(hfac)(2), Cu particles in the range of 60-95 nm formed on SiOx or TiN during the 5 min reduction period. As the Pd(hfac)(2) concentration increased to 5 mol% (relative to the amount of Cu(hfac)(2)center dot H(2)O), a morphology transition from particle formation to film formation was observed. When the Cu(hfac)(2)center dot H(2)O concentration varied from 0.1 wt% to 3 wt% at a fixed Pd(hfac)(2) concentration of 5 mol%, highly uniform, dense and adherent films with 10-40 nm in thickness were produced. Root mean square (rms) roughness of these films, estimated by AFM images, is in the range of 1.7-5.8 nm. Chemical composition analysis of 5 mol% Pd catalyzed Cu film by X-ray photoelectron spectroscopy (XPS) revealed that approximately the ratio of Pd to Cu incorporated into the film was two times larger than the initial Pd(hfac)(2) to Cu(hfac)(2)center dot H(2)O ratio.
Keywords: CHEMICAL-VAPOR-DEPOSITION; CARBON-DIOXIDE SOLUTION; IMMERSION DEPOSITION; FLUID DEPOSITION; NICKEL FILMS; METAL-FILMS; SILICON; METALLIZATION